Pintamos nuestro patrimonio : un proyecto de educación artística y patrimonial para educación infantil - Piña, Olga María Duarte (2018)
The challenge of this work is to combine heritage and artistic education to bring children’s education to their environment in a creative way, with the intention of being valued and taught how to conserve it. In relation to the artistic and patrimonial experience for the classrooms of 3, 4 and 5 years will explain the design of the project and the methodological model that supports it, the purposes of learning, what happens in each classroom in terms of experimentation, results and learning difficulties